Studi Etnopedagogi dalam Praktik Zikir Saman di Lombok Timur - Muslim, Asbullah (Jurnal Studi Agama dan Masyarakat, 2018)
Nowadays, Ethno pedagogy has a vital urgency in influencing the choices such as forms, ways and goals of an ongoing action. Ethno pedagogy can contribute in education based on cultural values for learning in the context of teaching as a cultural activity and culture of teaching. This study is aimed at describing the practice of Saman Zikr and share information about the role of Saman Zikr in implementing the values of cultural local wisdom in East Lombok. By using the method of synthesis analysis through structured and unstructured interviews, observation and documentation, this study reveals that Samman Zikr contains values, concepts and education contents based on ethno pedagogy deserving to be explored, interpreted, revitalized and developed as concepts and models of ethno pedagogic model in education and learning. The values of local wisdom as a source of innovation in the field of education on the basis of local community education are needed to empower through adaptation of local knowledge, reinterpretation of local wisdom values, revitalization in accordance with contemporary conditions, developing academic concepts and experimenting models in learning with ethno pedagogy.